The Duo of Osteogenic and Angiogenic Differentiation in ADSC-Derived Spheroids - Gorkun, Anastasiya A.; Revokatova, Daria P.; Zurina, Irina M.; Nikishin, Denis A.; Bikmulina, Polina Y.; Timashev, Peter S.; Shpichka, Anastasiya I.; Kosheleva, Nastasia V.; Kolokoltsova, Tamara D.; Saburina, Irina N. (Frontiers in Cell and Developmental Biology, 2021)
Bone formation during embryogenesis is driven by interacting osteogenesis and angiogenesis with parallel endothelial differentiation. Thence all in vitro bioengineering techniques are aimed at pre-vascularization of osteogenic bioequivalents to provide better regeneration outcomes upon transplantation. Due to appearance of cell-cell and cell matrix interactions, 3D cultures of adipose-derived stromal cells (ADSCs) provide a favorable spatial context for the induction of different morphogenesis processes, including vasculo-, angio- and osteogenesis, and therefore allow modelling their communication in vitro. However, simultaneous induction of multidirectional cell differentiation in spheroids from multipotent mesenchymal stromal cells (MMSCs) was not considered earlier. Here we show that arranging ADSCs into spheroids allows rapid and spontaneous acquiring of markers of both osteo- and angio-genesis as compared with 2D culture. We further showed that this multidirectional differentiation persisting in time, but not influenced by classical protocols for osteo- or angio-differentiation. At the same time, ADSC-spheroids retain similar morphology and microarchitecture in different culture conditions. These findings can contribute to a better understanding of the fundamental aspects of autonomous regulation of differentiation processes and their cross-talks in artificially created self-organizing multicellular structures. This, in turn, can find a wide range of applications in the field of tissue engineering and regeneration.